Potential adoption and diffusion of improved dual-purpose cowpea in the dry savannas of Nigeria: an evaluation using a combination of participatory and structured approaches - Okike, Iheanacho; Kristjanson, Patricia M.; Tarawali, Shirley A.; Singh, B.B.; Kruska, Russell L.; Mounyong, V.M. (International Institute of Tropical Agriculture, 2002)
The potential impact and return to investment from introducing improved dualpurpose cowpea for food and fodder in northern Nigeria was investigated using a combination of farmers' workshops and village and household level surveys. Out of the 462 households surveyed, 41 % were adopters, 9% had been adopters at one time but had stopped, while 50% had never tried improved dual-purpose cowpea. Three wealth classes were defined by the respondents themselves: the rich (13% of farmers), the middle class (60%), and the poor (27%). In all communities, middle class farmers led in adoption of improved varieties and in using recommended doses of insecticide sprays. Improved dual-purpose varieties contributed more to total value product (12%) than local varieties (11%) in spite of the fact that only 55% of adopters used insecticide sprays and that the area under local varieties was double that of improved varieties-23% compared to 13%. The results show that application of insecticide is a positive function related to the level of agricultural intensification of the system. The implication is that farmers should be encouraged to plant improved dual-purpose cowpea varieties without stressing that insecticides are mandatory. Such inputs can be introduced subsequently in response to the market environment and the status of crop-livestock interactions. This thrust has the potential to boost adoption and diffusion of improved dual-purpose cowpea varieties as well as overall production of cowpea. Estimates from a combination of geographic information systems (GIS) data and household-level surveys show that four million hectares of land are under cowpea in the dry savanna zone of Nigeria alone. When compared to existing figures (about four million ha for all Nigeria) it could be concluded that the .area under cowpea in Nigeria is being underestimated along with the contributions of cowpea to food security and livelihoods. Finally, the results indicate that while improved dual-purpose varieties are preferred in more rural areas with less market access but where livestock seem to make a higher contribution to crop-livestock systems and livelihoods, both improved grain and dual-purpose cowpea varieties have evenly high adoption rates in areas with good access to markets. Therefore, policies aimed at improving markets and roads have the highest potential payoffs in terms of speeding up the rate of adaption.